Determinants of Profit Sharing Financing and Zakat Distribution Based on CAMEL Analysis - Yetty Murni; Tri Astuti; Chaerani Nisa (University of Merdeka Malang, 2018)
The rapid development of Islamic banking has many positive impacts, but on the other hand, the development also demands the readiness of sharia banking in meeting the soundness level standard set by the regulator. This study aimed to integrate the two methods of measurement of Islamic financial institutions, the CAMEL method, and maqasid sharia method. How far the ability of CAMEL, macro and general measurement, in measuring the variables on the maqasid sharia. This research used a panel data model and analyzed four regressions model which welfare model for Sharia Commercial Bank and Sharia Business Unit and affordable product model for Sharia Commercial Bank and Sharia Business Unit. This research used the quantitative descriptive method. We found that only affordable product in Sharia Business Unit can explain independent variable. Other than that, earning component in CAMEL (ROA) had a positive and significant relationship with profit sharing scheme loan. From the results of research conducted, in general, CAMEL and maqasid sharia did not have a relationship except for Sharia Business Unit. This condition can happen because of many things. Among the greater was risked and in terms of better profitability. Therefore, Sharia Commercial Bank and Sharia Business Unit, generally still run a relatively low-risk financing scheme such as Murabaha.JEL Classification: G31, G32, G34DOI: https://doi.org/10.26905/jkdp.v22i4.1994